TYPES OF PREDICATES ACCORDING TO EXPRESSION AND STRUCTURE - Gʻaniqulov Joʻrabek Zohid oʻgʻli (International Journal of Literature and Language Studies, 2026)
This article addresses key issues causing problematic debates in modern Uzbek linguistics. It examines compound word structures, their classification, and how various parts of speech form different types of predicates—supported by practical exercises and analytical breakdowns. Furthermore, it highlights the distinct structural features differentiating verbal phrases from verbal predicates within grammatical linkages.